ZnO nanoparticles promote the malignant transformation of colorectal epithelial cells in APCmin/+ mice. (January 2022) - Meng, Jian; Yang, Juan; Pan, Ting; Qu, Xianjun; Cui, Shuxiang
Graphical abstract: Highlights: ZnO NPs induce chronic inflammation in colorectal mucosal epithelia. ZnO NPs promote malignant transformation of colonic cells in APC min/+ mice. ZnO NPs promote tumorigenesis through activating CXCR2. Free-zinc release of ZnO NPs promotes the malignant transformation. Abstract: As the use of zinc oxide nanoparticles (ZnO NPs) in everyday products grows, so does concern about health risks. However, no findings on the gastrointestinal toxicity of ZnO NPs have been published. We investigated the possible malignant transformation of ZnO NPs in the mice's colonic tissues using the APC min/+ mouse model with a premalignant lesion in intestinal epithelial cells. Higher doses and long-term oral exposure to ZnO NPs were found to mildly promote colonic inflammation in WT mice, while they moderately or strongly exacerbated the severity of chronic inflammation and tumorigenesis in APC min/+ mice with intestinal adenomatous polyposis. The ZnO NPs-induced inflammation and tumorigenesis in colonic epithelial cells was linked to the activation of CXCR2/NF-κB/STAT3/ERK and AKT pathways. Analysis of the ZnO NPs-exacerbated intestinal adenomatous polyposis in APC min/+ mice revealed that ZnO NPs could activate the APC -driven Wnt/β-catenin signaling pathway, exacerbating intestinal tumorigenesis. In fact, ZnO NPs have been shown to increase intestinal inflammation and tumorigenesis in APC min/+ mice by releasing free Zn 2+ . In WT mice, a low dose of ZnO NPs (26 mg/kg/day) did not cause intestinal inflammation. In conclusion, higher doses and prolonged exposure to ZnO NPs promote the malignant transformation of precancerous epithelial cells.